The Influence of Parasocial Interaction on Sense of Virtual Community of Chinese Series’ Fans - Ruangroengkulrit, Pathaya; Pornsakulvanich, Vikanda (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The goal of this research was to study the effect of generation on the level of parasocial interaction between series fans and to forecast the influence of parasocial interaction (PSI) and the Internet media usage on Sense of Virtual Community (SOVC) in the context of Chinese series fans,using quantitative research on the structure of uses and gratifications theory. An online survey was performed to gather data from 505 participants who were fans of Chinese series in Thailand. The findings revealed that Gen Y fans had a higher PSI degree than Gen X fans. It was also positively projected that PSI would affect both the level of Internet media use in watching Chinese series and the level of participation in virtual communities. Chinese series fans with a higher degree of PSI will use Internet media more often to watch Chinese series, participate in virtual communities,and spend more time watching series overall. Finally, it was also confidently expected that the frequency of internet media use to watch the series and the frequency and time taken to participate in virtual communities increased the degree of SOVC. This study has shown that the effect of PSI on online media use for a particular intent has contributed to the development of a strong virtual culture that can be used for social benefits, such as the creation of virtual communities for social support, and can be used for marketing advantages, including developing brand communities that can achieve a distributed target groups and increase brand loyalty.